1993
DOI: 10.1037/1064-1297.1.1-4.7
|View full text |Cite
|
Sign up to set email alerts
|

A psychopharmacology of motivation and reward related to substance abuse treatment.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 104 publications
1
10
0
Order By: Relevance
“…These results are consistent with previous findings that P rats engage in more operant responding with ethanol reinforcement than do HAD rats during continuous access (Files et al, 1998) and during limited access when a within-session progressive ratio procedure is used (Ritz et al, 1994b). Moreover, these results are consistent with and extend previous findings showing a distinction between (1) ethanol preference and ethanolreinforced responding and (2) ethanol-reinforced respond-ing and actual ethanol intake in operant paradigms after a variety of manipulations (e.g., increasing response requirement, changing ethanol concentration; George, 1990;George and Ritz, 1993;Ritz et al, 1994a;Samson, 1986;Samson et al, 1998aSamson et al, , 2001. The lack of a correlation between subjects' reinforcer intake and reinforcer seeking during both extinction and breakpoint sessions, regardless of line, also supports a distinction between the appetitive and consummatory processes and is consistent with our previous findings with a limited-access model (Samson et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with previous findings that P rats engage in more operant responding with ethanol reinforcement than do HAD rats during continuous access (Files et al, 1998) and during limited access when a within-session progressive ratio procedure is used (Ritz et al, 1994b). Moreover, these results are consistent with and extend previous findings showing a distinction between (1) ethanol preference and ethanolreinforced responding and (2) ethanol-reinforced respond-ing and actual ethanol intake in operant paradigms after a variety of manipulations (e.g., increasing response requirement, changing ethanol concentration; George, 1990;George and Ritz, 1993;Ritz et al, 1994a;Samson, 1986;Samson et al, 1998aSamson et al, , 2001. The lack of a correlation between subjects' reinforcer intake and reinforcer seeking during both extinction and breakpoint sessions, regardless of line, also supports a distinction between the appetitive and consummatory processes and is consistent with our previous findings with a limited-access model (Samson et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Both the P (Bice and Kiefer, 1990) and HAD (Kiefer et al, 1995) lines have been shown to "develop a taste" for ethanol after exposure as measured by an increase in palatability (taste reactivity) relative to their nonpreferring lines. However, there is considerable evidence from experiments using both selected lines and outbred rats that home cage ethanol drinking and ethanolreinforced operant responding procedures measure different components of the regulation of ethanol consumption (George, 1990;George and Ritz, 1993;Ritz et al, 1994a,b;Samson, 1986;Samson et al, 1998aSamson et al, , 2001.…”
mentioning
confidence: 99%
“…For example, Robinson and Berridge (1993) suggest that DA may mediate the wanting of a drug, whereas some other system (e.g., opiate or GABA-benzodiazepine systems) may mediate the liking. In contrast, George and Ritz (1993) propose that DA may mediate the rewarding (i.e., pleasurable) effects of drugs, whereas serotonin may mediate the motivation to take them. This issue is currently receiving considerable attention, and has yet to be empirically resolved.…”
Section: Interpretational Issuesmentioning
confidence: 86%
“…Conversely, however, Johanson and colleagues (1983) reported that over repeated administrations, amphetamine continued to produce reliable euphorigenic effects but behavioral preference for the drug (versus placebo) declined. The apparent dissociation between subjective and reinforcing effects has been used by some (Fibiger et al 1992;George and Ritz 1993;Robinson and Berridge 1993) to argue that liking a drug (e.g., positive subjective effects; euphoria) and wanting it (e.g., reinforcing effects) may have different neural substrates. For example, Robinson and Berridge (1993) suggest that DA may mediate the wanting of a drug, whereas some other system (e.g., opiate or GABA-benzodiazepine systems) may mediate the liking.…”
Section: Interpretational Issuesmentioning
confidence: 98%
“…These animals were selected based on the phenotype of 24 hr home cage ethanol (10%) intake and preference over concurrently available water (for reviews and details, see Li et al, 1994;Li and McBride, 1995;McBride and Li, 1998). However, there is considerable evidence from experiments using both selected lines and outbred rats that home cage ethanol drinking and ethanolreinforced operant responding procedures measure different components of the regulation of ethanol consumption (George, 1990;George and Ritz, 1993;Ritz et al, 1994a,b;Samson, 1986;Samson et al, 1998aSamson et al, , 2001. However, there is considerable evidence from experiments using both selected lines and outbred rats that home cage ethanol drinking and ethanolreinforced operant responding procedures measure different components of the regulation of ethanol consumption (George, 1990;George and Ritz, 1993;Ritz et al, 1994a,b;Samson, 1986;Samson et al, 1998aSamson et al, , 2001.…”
mentioning
confidence: 99%